Five ways to counter ableist messaging in medical education in the context of promoting healthy movement behaviours - Faught, Emma; Morgan, Tamara L; Tomasone, Jennifer R (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
One in five Canadians have a disability and there are well-documented gaps in care for this equity-deserving group that have roots in medical education. In this paper, we highlight the unintended consequences of ableist messaging for persons living with disabilities, particularly in the context of promoting healthy movement behaviours. With its broad reach and public trust, the medical community has a responsibility to acknowledge the reality of ableism and take meaningful action. We propose five strategies to counter ableist messaging in medical education: (1) increase knowledge and confidence among physicians and trainees to optimize movement behaviours in persons living with disabilities, (2) perform personal and institutional language audits to ensure terminology related to disability is inclusive and avoids causing unintended harm, (3) challenge ableist messages effectively, (4) address the unmet healthcare needs of persons living with disabilities, and (5) engage in efforts to reform medical curricula so that persons living with disabilities are represented and treated equitably. Physicians and trainees are well-positioned to deliver competent and inclusive care, making medical education an opportune setting to address health inequities related to disability.